J-PAS: forecasts on interacting dark energy from baryon acoustic oscillations and redshift-space distortions. Issue 1 (1st July 2019) - Costa, A A; Marcondes, R J F; Landim, R G; Abdalla, E; Abramo, L R; Xavier, H S; Orsi, A A; Devi, N Chandrachani; Cenarro, A J; Cristóbal-Hornillos, D; Dupke, R A; Ederoclite, A; et al.
ABSTRACT: We estimate the constraining power of Javalambre-Physics of the Accelerated Universe Astrophysical Survey (J-PAS) for parameters of an interacting dark energy (DE) cosmology. The survey is expected to map several millions of luminous red galaxies, emission line galaxies, and quasars in an area of thousands of square degrees in the northern sky with precise photometric redshift measurements. Forecasts for the DESI and Euclid surveys are also evaluated and compared to J-PAS. Using the Fisher matrix approach, we find that J-PAS can place constraints on the interaction parameter comparable to those from DESI, with an absolute uncertainty of about 0.02, when the interaction term is proportional to the dark matter energy density, and almost as good, of about 0.01, when the interaction is proportional to the DE density. For the equation of state of DE, the constraints from J-PAS are slightly better in the two cases (uncertainties 0.04–0.05 against 0.05–0.07 around the fiducial value −1). Both surveys stay behind Euclid but follow it closely, imposing comparable constraints in all specific cases considered.